Sarcoid-like reaction in Cryptococcus neoformans infection. (30th July 2012) - Yano, Shuichi; Kobayashi, Kanako; Ikeda, Toshikazu; Kadowaki, Toru; Wakabayashi, Kiryo; Kimura, Masahiro; Ishikawa, Shigenori; Adachi, Yoshin; Araki, Kunio; Nagaoka, Saburo
Abstract : We report a patient with Cryptococcus (C.) neoformans infection, who developed a case of sarcoid-like reaction (SLR). There have been reports of SLRs associated with malignancies. Although differentiating sarcoidosis from SLR is difficult, the patient was diagnosed as SLR because propionibacterium acnes bacterial (PAB) antibody staining of biopsy specimens was negative and the chest radiological findings improved after antifungal treatment. To our knowledge, this is the first report of SLR occurring during cryptococcal infection, and we believe that cryptococcal infection should be considered as a potential cause of SLR.